ANALISIS PERLINDUNGAN HUKUM TERHADAP DATA PRIBADI DALAM TRANSAKSI E-COMMERCE - Samuel Christian Salim; Jeane Neltje (Jurnal Hukum Adigama, 2021)
The rise of online shopping also causes a new problem in the legal field, especially consumer protection law. One of the problems that must be considered in terms of online shopping is the legal protection of the personal data of consumers who shop online. This problem exists because it is easy for business actors to get personal data of consumers who shop online. Business actors get consumer personal data when consumers transact online. In conducting online transactions, of course, consumers must first fill in personal data in order to achieve smooth buying and selling transactions and fill in personal data as well as to fulfill the requirements for conducting online transactions. One clear evidence of the leakage of personal data is in the case of the leak of personal data on the Akulaku platform. Akulaku is slightly different from other platforms where Akulaku also provides installment services or cash loans on an independently managed online marketplace platform. One of the most common cases involving consumers of e-commerce users is the misuse of users' personal data by third parties. Like the case that happened to Dewa Hardana in the middle of 2020. Dewa Hardana is one of the victims of misuse of personal data in the Akulaku application, in which case Dewa Hardana's personal data is misused by a third party and Dewa Hardana must bear the loss.